Study on the Effect of Dietary Hemp Seed Powder Doses on Certain Reproductive Hormones in Iraqi Awassi Ewes - Omer, Esam Saeed; Rebat, Salam Ketab; ZinAlabidin, Mohammed Madhi (American Journal of Botany and Bioengineering, 2025)
This study focused on examining how Russian hemp seeds affect specific reproductive hormones in Iraqi Awassi ewes. A total of twelve local Awassi ewes, ages between three and four years, It was selected and distributed into three experimental groups, each consisting of four ewes with similar body weights. Each ewe acted as an individual replicate. The groups were randomly assigned to each of the three treatment conditions: the first group (Control - T1) received no extra supplements; the second group (T2) was given a daily dose of 200 mg of powdered hemp seeds mixed with corn flour, which was administered in gelatin capsules; the third group (T3) received the same supplement as T2 but at a higher daily dosage of 300 mg. The treatment lasted for 45 days. No statistical differences (P>0.05) were detected in the levels of estrogen, LH, FSH, and prolactin in serum between groups. From the results obtained in current study, Level of hemp seed powder used (200 and 300 mg/ewe/day) are physiologically safe for Awassi ewes included in this study.